2014
DOI: 10.1002/acr.22205
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Anti–Tumor Necrosis Factor Biologic Agents in Human T Lymphotropic Virus Type I–Positive Patients With Rheumatoid Arthritis

Abstract: Objective. To investigate the response to and safety of anti-tumor necrosis factor (anti-TNF) therapy in human T lymphotropic virus type I (HTLV-I)-positive patients with rheumatoid arthritis (RA).Methods. Therapeutic response was evaluated in 10 HTLV-I-positive and 20 HTLV-I-negative patients with RA (sex and age matched) at 3 months after the beginning of anti-TNF therapy using the European League Against Rheumatism improvement criteria. As secondary end points, the discontinuation rate of anti-TNF therapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…There is always the worry of ATLL development if immune-modulatory drugs, such as TNF-a, which are standard treatment for RA, are used. There are reassuring reports on TNF-a blockers, although it seems to be less effective in HTLV-1 positive patients [207,208]. Rituximab and etanercept have been used [209], but need to be verified in clinical trials.…”
Section: Htlv-1 Associated Arthritismentioning
confidence: 99%
“…There is always the worry of ATLL development if immune-modulatory drugs, such as TNF-a, which are standard treatment for RA, are used. There are reassuring reports on TNF-a blockers, although it seems to be less effective in HTLV-1 positive patients [207,208]. Rituximab and etanercept have been used [209], but need to be verified in clinical trials.…”
Section: Htlv-1 Associated Arthritismentioning
confidence: 99%
“…The HTLV‐I virus infects primarily CD4+ T lymphocytes but also synovial fibroblasts and salivary gland epithelial cells, and HTLV‐I infection can modify the functions of these cells . In this context, a previous study by our group that was conducted in an area endemic for HTLV‐I infection showed that HTLV‐I – positive patients with RA are more resistant to TNF inhibitors compared with HTLV‐I – negative RA patients .…”
mentioning
confidence: 99%
“…In a previous study by our group , we compared the response to TNF inhibitors in 10 HTLV‐I–positive RA patients with that in 20 HTLV‐I–negative patients with RA (matched for age and sex), in a single area with a high prevalence of HTLV‐I, Miyazaki Prefecture. We observed that the treatment outcomes were generally affected by several background elements, such as disease activity at the start of treatment and positivity for rheumatoid factor (RF) or anti–citrullinated protein antibodies (ACPAs).…”
mentioning
confidence: 99%
“…They showed no indication of developing ATLL during a 2-year observation period. 2 Furthermore, HTLV-1-infected cells from patients with HTLV-1-associated myelopathy showed no significant inflammatory cytokine profiles by anti-tumour necrosis factor-a inhibitor. 3 These findings suggest that the inhibition of anti-tumour necrosis factor-a has no influence on the development of ATLL.…”
Section: Discussionmentioning
confidence: 95%